21st century economics a reference handbook - Free, Rhona C.; Gale Group (Thousand Oaks, California SAGE, 2010)
"Provides summaries of theory and models in key areas of micro and macroeconomics. Topics include an introduction to relevant theory and empirical evidence.""--GVRL description.
v. 1, pt. 1. Scope and methodology of economics ; pt. 2. Microeconomics ; pt. 3. Public economics ; pt. 4. Macroeconomics ; pt. 5. International economics -- v. 2, pt. 6. Economic analyses of issues and markets ; pt. 7. Emerging areas in economics.
Electronic reproduction.
Keywords: Economics -- Handbooks, manuals, etc; Electronic books